Nutritive Value and Mineral Elements of Wild Astragalus meridioalis sensu auct. Seeds in South of Iran - Elahe Rahimi; Jinous Asgarpanah; Parisa Ziarati (Islamic Azad University, 2017)
Literature survey revealed that there was no biological investigation on Astragalus meridioalis sensu auct. seeds worldwide. The mature seeds of A. meridioalis was collected in August 2015 from Geno, Bandar Abbas, Hormozgan Province, Iran to evaluate their nutritional value and explore a new source for nutritional purposes .The digested seeds of A. meridioalis with the mixture of nitric acid and hydrochloric acid and per chloride acid (4 :2: 1) under the condition of the boiling point and the normal pressure, the contents of the seven mineral elements necessary to humanity, potassium, copper, zinc, iron, selenium , lithium and manganese in the seeds of A. meridioalis were determined by flame atomic absorption spectroscopy (FAAS) in Pharmaceutical sciences branch, Islamic Azad university , Tehran and the results were analyzed in statistics. The results revealed that the sequence of the content of metal elements is as follows in all samples: Zn >K > Fe > Cu> Mn >Ca>Na > Se > Li. The content of K, Zn, Fe and Cu in this seed is much richer than some other medicinal plants in this region. The high level of Zinc, Potassium and sufficient amount of suitable mineral element showing high Nutritive value of this seed and seem to be good for younger people, anemic people and common local food and diet for people in the region of Hormozgan province in the south of Iran.